2014
DOI: 10.1186/1471-2105-15-119
|View full text |Cite
|
Sign up to set email alerts
|

ConSole: using modularity of Contact maps to locate Solenoid domains in protein structures

Abstract: BackgroundPeriodic proteins, characterized by the presence of multiple repeats of short motifs, form an interesting and seldom-studied group. Due to often extreme divergence in sequence, detection and analysis of such motifs is performed more reliably on the structural level. Yet, few algorithms have been developed for the detection and analysis of structures of periodic proteins.ResultsConSole recognizes modularity in protein contact maps, allowing for precise identification of repeats in solenoid protein str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Although ProStrip [26] and CE-Symm [30] have relatively high rate of True Positive cases, they also generate an unsatisfactory high number of false positives. The benchmark also showed that RAPHAEL [19] and ConSole [20], in general, have lower rates of both True Positive and False Positive prediction. This can be explained by the fact that they are mainly designed to predict specific classes of 3D TRs, therefore, fail to find the other existing types of TR structures.…”
Section: Benchmarking Of Tapo Against Cutting Edge 3d Tr Prediction Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ProStrip [26] and CE-Symm [30] have relatively high rate of True Positive cases, they also generate an unsatisfactory high number of false positives. The benchmark also showed that RAPHAEL [19] and ConSole [20], in general, have lower rates of both True Positive and False Positive prediction. This can be explained by the fact that they are mainly designed to predict specific classes of 3D TRs, therefore, fail to find the other existing types of TR structures.…”
Section: Benchmarking Of Tapo Against Cutting Edge 3d Tr Prediction Mmentioning
confidence: 99%
“…In recent years, efforts have been made to develop bioinformatics tools for the detection and analysis of repetitive elements in protein structures (3D TRs) such as feature-based learning methods RAPHAEL [19] and ConSole [20], a method for tiling structural space [21], a Fourier analysis method by Taylor et al [22], wavelet transforms [23], signal analysis methods: DAVROS [24] and OPASS [25], methods that use conformational alphabets (ProStrip [26] and Swelfe [27]), and miscellaneous methods such as AnkPred [28], IRIS [29] and CE-Symm [30]. In the next section, we survey these approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swelfe (Abraham et al 2008) and ProSTRIP (Sabarinathan et al 2010)). RAPHAEL generates geometric profiles based on Cα coordinates and uses them in combination with support vector machine (SVM) to mimic visual interpretation of a manual expert and classifies a protein into solenoid/non-solenoid class (Walsh et al 2012), while graph based approach, ConSole (Hrabe and Godzik 2014), uses a rule based machine learning technique to identify solenoid repeats in proteins. TAPO (TAndem PrOtein detector) (Do Viet et al 2015) considers various structural features such as periodicities of atomic coordinates, strings generated by conformational alphabets, residue contact maps and arrangements of vectors of secondary structure elements to build a prediction model using SVM for identification of structural repeats.…”
Section: Introductionmentioning
confidence: 99%
“…of PRIGSA2 algorithm is compared with four state-of-the-art repeat detection algorithms, namely, REPETITA(Marsella et al 2009), ConSole(Hrabe and Godzik 2014),TAPO (Do Viet et al 2015) and RepeatsDB-lite, and its previous version (PRIGSA(Chakrabarty and Parekh 2014c)). ConSole applies image processing on contact map representation of protein structure and uses a trained SVM to identify repeats, while TAPO ranks the predictions from various sequence and structure based methods on a SVM classifier to identify repeats.…”
mentioning
confidence: 99%